2018
DOI: 10.3892/ijo.2018.4607
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase�1 promotes the metastasis of colorectal cancer by inducing the epithelial‑mesenchymal transition mediated by the FAK/AKT/MMPs axis

Abstract: It was demonstrated that Sphingosine kinase 1 (SphK1) promotes tumor progression and confers the malignancy phenotype of colorectal cancer by activating the focal adhesion kinase (FAK) pathway. However, further clarification is required to determine if SphK1 promotes the metastasis of colorectal cancer by inducing epithelial-mesenchymal transition (EMT), and its mechanisms have not been fully elucidated. Immunohistochemistry staining was used to detect protein expression in normal colonic mucosa tissues and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 38 publications
2
50
0
Order By: Relevance
“…Constitutively active G q/11 proteins act as oncogenes [ 59 ], and thus given the role of SphK1 in cancer, it will be interesting to unravel a possible interconnection. Another important theme is the emerging role of SphK1 in epithelial–mesenchymal transition [ 60 , 61 ]; however, it should be kept in mind that besides G q/11 proteins, there are many other pathways regulating SphK1 expression and activity, and which may be important in this context. Nevertheless, we strongly believe that unravelling the mechanism(s) by which G q/11 regulates SphK1 will further help to understand the functional roles of this enzyme and facilitate its targeting by potential therapeutics.…”
Section: Resultsmentioning
confidence: 99%
“…Constitutively active G q/11 proteins act as oncogenes [ 59 ], and thus given the role of SphK1 in cancer, it will be interesting to unravel a possible interconnection. Another important theme is the emerging role of SphK1 in epithelial–mesenchymal transition [ 60 , 61 ]; however, it should be kept in mind that besides G q/11 proteins, there are many other pathways regulating SphK1 expression and activity, and which may be important in this context. Nevertheless, we strongly believe that unravelling the mechanism(s) by which G q/11 regulates SphK1 will further help to understand the functional roles of this enzyme and facilitate its targeting by potential therapeutics.…”
Section: Resultsmentioning
confidence: 99%
“…13 As a critical mediator that connects integrin and the downstream signaling molecules, FAK can be activated by integrin phosphorylation and subsequently activates downstream PI3K/ AKT pathway and MAPK pathway. [14][15][16][17][18][19][20][21] To validate whether OSR1 exerts anti-cancer effects via FAK in COAD, we detected the activation of FAK based on p-FAK level. The results indicated that OSR1 overexpression inhibited the activation of FAK.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, sphingosine kinase (SphK) -1, an oncogenic kinase, has attracted increasing attention because of its important functions in many processes of cancer cells [12][13][14]. A few studies showed that SphK1 might mediate the EMT of A549 cells, but the mechanisms remain ambiguous [15][16].…”
Section: Introductionmentioning
confidence: 99%